Efficacy of Adjunctive Antiseptic Lavage Solution in Managing Acute Hip/Knee Prosthetic Joint Infection: A Comparative Study in a Tertiary Revision Center - Jonathan Quinn, FRACS; Bernard H. van Duren, DPhil, FRCS; Reshid Berber, PhD, FRCS; Mark Higgins, FRCS; Hosam E. Matar, FRCS; Andrew R. Manktelow, FRCS; Benjamin V. Bloch, FRCS (Arthroplasty Today)
Background: Debridement, antibiotics and implant retention (DAIR) procedure is well-established as a management option for acute periprosthetic joint infection (PJI). We investigated the infection eradication rates of DAIR procedures at our center using Bactisure wound lavage. Methods: A retrospective consecutive review of DAIR procedures for hip and knee PJI was conducted between 2018 and 2023 with a minimum 12-month follow-up at our tertiary revision arthroplasty center. Suitability for DAIR was determined at the multi-disciplinary team discussion. Revision procedures and patients with previous PJI were excluded. Patient, surgical, microbiological, and postoperative data (minimum 12 months) was reviewed. The use of Bactisure was in addition to routine surgical management. Results: During the study period, 76 DAIR procedures were performed (55 knees and 21 hips). Bactisure was used in 26 cases (20 knees and 6 hips). Overall, 6 of 26 Bactisure DAIRs failed (23%), while 14 of 50 non-Bactisure DAIRs failed (28%), which did not demonstrate statistical significance (P = .644). Subgroup analysis demonstrated no difference in knee DAIRs (P = .761) but a trend toward significance in hip DAIRs (P = .262). No adverse effects of Bactisure use were noted intraoperatively or postoperatively. DAIR failed in 50% of diabetic patients compared to 20% of nondiabetic patients (P = .015). Age, body mass index, and organism identification did not influence outcome. Conclusions: The addition of Bactisure to DAIR procedures did not demonstrate statistically significant improvement of successful eradication of infection, but a potential trend toward significance was noted in hip DAIRs. Diabetic patients failed DAIR in 50% of cases. The in-vivo outcomes of Bactisure use during DAIR procedures remain inconclusive.